TINJAUAN YURIDIS TERHADAP KEABSAHAN PEMBUATAN AKTA JUAL BELI TANAH OLEH PEJABAT PEMBUATAN AKTA TANAH YANG DIDUGA DIBUAT SECARA MELAWAN HUKUM (Studi Putusan Pengadilan Palembang No. 214 k/Pdt/2021) - Ashanti Nurshafira; Mohamad Fajri Mekka Putra (The Juris, 2022)
This research discusses the benchmarks in determining the establishment of the deed of sale and purchase of land which is considered to be determined whether it is against the law or not and the legal force of the certificate as the evidence, based on the decision of the District Court Number 214 k/Pdt/2021. The case was occured in Palembang, specifically in the Palembang District Court. The types and sources of the data that will be used in writing this research are divided into two, namely primary data and secondary data. In writing this research, there are two data collection techniques used which is library research and field research. The data obtained both primary and secondary data were analyzed using quantitative techniques and then presented descriptively. The credibility of the deed is questionable because the Land Deed Making Officer as a General Officer (hereinafter referred to as "PPAT") is suspected of helping one party to gain profit and making a deed which is not in accordance with the existing facts. This causes the deed to be deemed to have been made against the law as regulated in Article 1365 of the Civil Code. Acts against the law in PPAT are essentially carried out if the making of the deed is contrary to legal norms and authorities, obligations and prohibitions in making the deed. This violation also results in losses suffered by one of the parties. For this reason, it is necessary to analyze how the benchmark for making a deed by PPAT can be made against the law and how the strength of certificate evidence is in the eyes of the law in a dispute.